Some open questions and prospects for co-operation of the Danube-basin countries - Vajs-Stojić-Karanović Edita (Međunarodni Problemi)
The author points to the fact that the basic problem in the field of co-operation among the Danube-basin countries is the insufficiency of mutual economic relations between them. It is necessary to encourage creation of bilateral and multilateral forms of co-operation among the Danube-basin countries and establishment of their common approach to the other regions of the world. There is also a need for inflow of world capital, considering that the principles of sustainable exploitation of natural resources (sustainable development) are respected. All these efforts should be directed towards achievement of more accelerated economic development, to attain growth of labour productivity, to increase employment rate and the standard of living, to achieve development of national cultures and their mutual interweaving, and thus to ensure growth of material and cultural wealth of any defined community and the region as a whole.